The Transition of Indonesian Citizenship to Thai Citizenship from a Civil Law Perspective - Kurniawan, M. Teguh; Nurhilmiyah (Universitas Islam Negeri Alauddin Makassar, 2026)
The transition of citizenship from Indonesian citizenship to Thai citizenship represents a complex legal phenomenon involving the interaction of two different national legal systems with significant consequences in the civil law domain. Citizenship functions not only as a political status but also as a juridical bond that determines an individual’s personal law, legal capacity, property rights, family relations, and inheritance regime. This study aims to analyze the legal procedures governing the relinquishment of Indonesian citizenship and the acquisition of Thai citizenship, as well as to examine the civil law implications arising from such transition from a comparative legal perspective. The research employs normative legal methods with a functional comparative law approach, relying on statutory regulations, legal doctrines, and scholarly literature related to citizenship law, civil law, and private international law in Indonesia and Thailand. The findings indicate that Indonesian law emphasizes the formal and administrative aspects of citizenship loss, while Thai law focuses on selective naturalization requirements and substantive integration. This asymmetry creates potential procedural gaps during the transitional phase that may expose individuals to legal uncertainty and risks of temporary statelessness. Furthermore, the transition of citizenship results in a fundamental transformation of civil legal status, including the loss of nationality-based rights in Indonesia, particularly land ownership rights, and the simultaneous acquisition of full civil rights under Thai law. The study concludes that citizenship transition constitutes a comprehensive legal transformation affecting the entire framework of civil rights and obligations rather than merely a change of nationality. Strengthening procedural synchronization, legal awareness, and cross-border administrative coordination is therefore essential to ensure legal certainty, protection of individual rights, and prevention of statelessness during the citizenship transition process.